Strategic Approaches to Fulfill Accreditation Quality Standards: A Case Study of High Schools in Tarakan City - Tri Agus Sutantia; Udik Budi Wibowo (STAI Hubbulwathan Duri, 2025)
This study examines strategies employed by high schools in Tarakan City to prepare for accreditation and ensure quality standards. A qualitative approach was adopted, involving seven key informants: accreditation coordinators from SMA Negeri 4 Tarakan City, SMK Negeri 4 Tarakan, and SMA NU 1 Tarakan City; two assessors from BAN-S/M North Kalimantan Province; the chair of BAN-S/M North Kalimantan Province; and a representative from the Education and Culture Office of North Kalimantan Province. Data were collected through interviews and document analysis and processed using an interactive model comprising data collection, condensation, display, and conclusion drawing. The study identified three key strategies: (1) forming an accreditation team to coordinate efforts, (2) managing data and information systematically, and (3) maintaining adequate facilities and infrastructure. These strategies underscore the importance of comprehensive preparation before accreditation assessments. The findings highlight the critical role of government support, team coordination, and infrastructure adequacy in addressing accreditation challenges. However, external factors such as geographical conditions, community involvement, and policy effectiveness were not explored, presenting a limitation. This study provides actionable insights for improving school accreditation processes and ensuring sustainable quality assurance. Future research should consider external and environmental factors to develop more comprehensive strategies.